Efficacy of oral brush biopsy in the early detection of oral cancer and oral potentially malignant disorders - a systematic review - Mahesh Shenoy (Wolters Kluwer Medknow Publications, 2022)
Introduction: Oral cancer is one of the most prevalent cancers in South East Asian countries due to increased consumption of tobacco products and alcohol and ranks sixth among the malignancies worldwide. Several screening modalities such as toluidine blue, Lugol's iodine staining, exfoliative cytology, and biopsy are being used to detect suspicious oral potentially malignant disorders (PMDs) at an early stage. Oral brush biopsy is a painless and less invasive technique that uses variations of a small brush to collect cells from all three layers of epithelium. The technique is non-invasive and promises to be an adjunct to the gold-standard histopathological examination and diagnosis of oral PMD. Aim: The aim of this systematic review was to compile studies pertaining to diagnostic utility of oral brush biopsy with or without computer-assisted cytological analysis in the screening of innocuous oral PMDs for early detection of cancerous changes. Materials and Methods: Computerized literature search was performed to select eligible articles from the following databases: PubMed (MEDLINE), GOOGLE SCHOLAR, and SCIENCE DIRECT using specific keywords. The search was limited to articles published as full text in English, which were screened by two reviewers for eligibility. Results and Discussion: Six studies satisfied our inclusion criteria and found oral brush biopsy as a moderately reliable screening tool for early detection of dysplastic changes in oral PMDs. For oral brush biopsy, sensitivity and specificity obtained were 97.7% and 84.5%, respectively, in the detection of high-grade dysplasia. Conclusion: Brush cytology using a cytobrush is a reliable adjunct to histopathology in detecting oral premalignant and malignant oral lesions. Specificity and sensitivity of the technique requires further investigative clinical studies.